Heat Acclimation Provides Sustained Improvement in Functional Recovery and Attenuates Apoptosis after Traumatic Brain Injury. Issue 11 (November 2015) - Umschweif, Gali; Shein, Na'ama A; Alexandrovich, Alexander G; Trembovler, Victoria; Horowitz, Michal; Shohami, Esther
Correction to : Journal of Cerebral Blood Flow and Metabolism (2010)30, 616–627; doi:10.1038/jcbfm.2009.234; published online 11 November 2009. Following the publication of this article, the authors noticed that Dr Umschweif was misspelled. The complete and correct author names appear above.